1995
DOI: 10.1590/s0037-86821995000200004
|View full text |Cite
|
Sign up to set email alerts
|

Estudo comparativo da freqüência da morte súbita inesperada por doença de Chagas, em Uberaba, nos anos de 1980 e 1990

Abstract: A comparison was made between the years 1980 and 1990 for the frequency and causes of sudden death occurring in the urban and rural areas of the city of Uberaba in individuals older than 15 years. It aims mainly to analyse the current frequency of sudden death in that region and to evaluate the impact, it any, of prophylaxis and therapy on sudden death due to Chagas' disease. For the 1226 deaths cases studied from our 1980, 54 (4.4%) were sudden ones; out of these, 13 (24.1%) were supposedly due to Chagas' dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Studies realized by the author during 1980, in an endemic area of American trypanosomiasis (Lopes & Chapadeiro 1983) indicated that CD was responsible for 24.1% of the SUD in the city of Uberaba. A similar study carried out 10 years later (Lopes et al 1995) showed that the frequency of this type of SD had fallen to 6.8%. Data gathered in a field study (Macedo 1973) suggested that SUD occurs in approximately 37.5% of the chagasic patients which live in endemic areas.…”
Section: Frequency General Characteristics and Importance Of Sudden mentioning
confidence: 73%
“…Studies realized by the author during 1980, in an endemic area of American trypanosomiasis (Lopes & Chapadeiro 1983) indicated that CD was responsible for 24.1% of the SUD in the city of Uberaba. A similar study carried out 10 years later (Lopes et al 1995) showed that the frequency of this type of SD had fallen to 6.8%. Data gathered in a field study (Macedo 1973) suggested that SUD occurs in approximately 37.5% of the chagasic patients which live in endemic areas.…”
Section: Frequency General Characteristics and Importance Of Sudden mentioning
confidence: 73%
“…Moreover, sudden cardiac death due to Chagas' disease represents up to 7% of total mortality as assessed by death certificates in areas where the disease is endemic [13]. The incidence of sudden cardiac death in a general, unselected cohort of patients with Chagas' disease may be as high as 5% annually [14].…”
Section: Epidemiologymentioning
confidence: 99%